Near Field Communication - Kevin Curran; Amanda Millar; Conor Mc Garvey (Institute of Advanced Engineering and Science, 2012)
Near Field Communication (NFC) is a technology that enables a device to communicate with another at a maximum distance of around 20cm or less. Currently, mobile phone manufacturers, banking institutions and mobile network providers are attempting to apply this technology to Smartphones and other handheld devices because of the opportunity to enable the consumer to use commercial services more easily. This paper discusses the expected increase in mobile payments using Near Field Communication, possible uses and the risks associated with carrying out transactions over a wireless network. We also discuss a real world implementation of an NFC based loyalty card system for retail.DOI:http://dx.doi.org/10.11591/ijece.v2i3.234